Delayed effects of a single-dose whole-brain radiation therapy on glucose metabolism and myelin density: a longitudinal PET study. (1st September 2020) - Parente, Andrea; Maciel, Elisa Scandiuzzi; J. O. Dierckx, Rudi A.; Langendijk, Johannes A.; de Vries, Erik F. J.; Doorduin, Janine
Abstract: Purpose: Radiotherapy is an important treatment option for brain tumors, but the unavoidable irradiation of normal brain tissue can lead to delayed cognitive impairment. The mechanisms involved are still not well explained and, therefore, new tools to investigate the processes leading to the delayed symptoms of brain irradiation are warranted. In this study, positron emission tomography (PET) is used to explore delayed functional changes induced by brain irradiation. Materials and methods: Male Wistar rats were subjected to a single 25-Gy dose of whole brain X-ray irradiation, or sham-irradiation. To investigate delayed effects of radiation on cerebral glucose metabolism and myelin density, 18 F-fluorodeoxyglucose ( 18 F-FDG) PET scans were performed at baseline and on day 64 and 94, whereas N- 11 C-methyl-4, 4′-diaminostilbene ( 11 C-MeDAS) PET scans were performed at baseline and on day 60 and 90 post-irradiation. In addition, the open field test (OFT) and novel spatial recognition (NSR) test were performed at baseline and on days 59 and 89 to investigate whether whole brain irradiation induces behavioral changes. Results: Whole-brain irradiation caused loss of bodyweight and delayed cerebral hypometabolism, with 18 F-FDG uptake in all brain regions being significantly decreased in irradiated rat on day 64 while it remained unchanged in control animals. Only amygdala and cortical brain regions of irradiated rats still showed reduced 18 F-FDG uptake on day 94. 11 C-MeDAS uptake in control animals was significantly lower on days 60 and 90 than at the baseline, suggesting a reduction in myelin density in young adults. In irradiated animals, 11 C-MeDAS uptake was similarly reduced on day 60, but on day 90 tracer uptake was somewhat increased and not significantly different from baseline anymore. Behavioral tests showed a similar pattern in control and irradiated animals. In both groups, the OFT showed significantly reduced mobility on days 59 and 89, whereas the NSR did not reveal any significant changes in spatial memory over time. Interestingly, a positive correlation between the NSR and 11 C-MeDAS uptake was observed in irradiated rats. Conclusions: Whole-brain irradiation causes delayed brain hypometabolism, which is not accompanied by white matter loss. Irradiated animals showed similar behavioral changes over time as control animals and, therefore, cerebral hypometabolism could not be linked to behavioral abnormalities. However, spatial memory seems to be associated with myelin density in irradiated rats.